GENDER DAN PEMBANGUNAN KOTA DI DUNIA - Faradiba Faradiba; M. Ilhamsyah Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
AbstractThis study aims to examine how the relationship between gender and urban development. The method used is qualitative analysis method using City Prosperity Index (CPI) data published by UNHABITAT year 2016. From the data selected 34 city with complete data for deep study. Based on the results of the research, found the fact of gender development is not subtle in cities with very high and high CPI led to improved urban development. In cities with moderate CPI, gender development channels are already visible, which are building moderate cities. In cities with low and very low CPI, gender development is clearly visible and bad. Poor gender development is highly visible in cities with very low CPI. The implications are the things people do to build cities, to improve the quality of urban development. In addition, it is also necessary to focus on urban development in pockets of poverty such as Sub-Saharan Africa, Latin America and Central and South Asia.Keywords: Gender Development, City Development, City Prosperity